Strategi dan Etika Dakwah Rasulullah SAW - RS, Syamsudin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2009)
Trip missionizes crowded rasulullah saw empirically fruitfulness. Strategy missionizes that reflect ethical point and gives motodiss framework universal is of important to be made reference and guidance by pengemban missionizes and be made as model of mission that have normative kontekstuals historical force. Severally behavioural ethical prophet which can make universal a figure of speech in missionizes for example (1 ) really regard situations and condition of, (2 ) Advances ahlakul karimah in acts, (3 ) Paying Attention impacts or effect of spontaneous actions.